Synthesis of a GlcNAcylated arginine building block for the solid phase synthesis of death domain glycopeptide fragments. Issue 11 (1st June 2017) - Wang, Siyao; Corcilius, Leo; Sharp, Phillip P.; Payne, Richard J.
Graphical abstract: Abstract: Herein we describe the synthesis of glycopeptide fragments from the death domains of TRADD and FADD bearing the recently discovered Nω -GlcNAc-β-arginine post-translational modification. TRADD and FADD glycopeptides were accessed through the use of a suitably protected synthetic glycosylamino acid 'cassette' that could be directly incorporated into conventional solid phase peptide synthesis (SPPS) protocols.